Women economic participation in novel Tentang Kamu by Tere Liye - Naililhaq, Fikha Nada; Udasmoro, Wening (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
The issue of the women’s role in the public sphere has been widely carried out in literary research. However, research on women's participation specifically on economic issues by looking at its theoretical and empirical aspects is still something that is very rarely carried out in literary research. The purpose of this study is to explore in more detail about women's participation in the economy. By using the lens of women's thinking and their participation in the economic field in the concept of women economic participation from Jacqui True, this research focuses on this issue. The method used is analyzing the content of the story that has been done by collecting data by collecting words, sentences, paragraphs related to women's participation in the economy. Furthermore, the data that have been found are analyzed using descriptive analysis methods. The descriptive method of analysis was carried out in several stages. The first stage is data collection which is done by collecting the aspects of women's participation in the economy in general in the data table. From the data table, it is classified according to the economic participation patterns found. The next stage is data analysis by dialogue data from the novel with the theory of women's participation in the economy. The results of this study indicate that women are able to get out of the crisis with their own efforts and hard work. Women also have an important role in the economic sector because they are able to create their own business opportunities so that they can improve their life.